Exploiting Optical Chaos for Color Image Encryption and Secure Resource Sharing in Cloud - Lili Li; Yiyuan Xie; Yuzhu Liu; Bocheng Liu; Yichen Ye; Tingting Song; Yushu Zhang; Yong Liu (IEEE Photonics Journal)
Cloud as a developing technology provides convenient services to sharing and usage of images resource, but brings a threat to images security and privacy authentication. Optical chaos possess distinct superiority for image secure sharing, therefore, based on two mutually coupled semiconductor lasers (MC-SL1 and MC-SL2), we theoretically propose a color image encryption system for secure resource sharing and introduce a watermarking method for images privacy authentication in cloud. In our paper, after achieving chaos synchronization under proper parameters, two MC-SLs are used to transmit encryption/decryption key space generated by chaotic signal of MC-SL1 and user's key. We carry out digital watermarking and encryption of a color image before secure resource sharing in cloud. On the other side of cloud, we make some tests for decryption of color image by received key space and watermark extraction. Meanwhile, we discuss security performance of color image encryption/decryption and key space transmission process, and analyze secure resource sharing of color image in cloud.